Effect of gibberellic acid and eggshell on Hylocereus polyrhizus - Phin, Yin Sin; Suat, Hian Tan; Zhe, Cheng Ng; Nyuk, Ling Ma; Wan Nurul Hidayah Wan Anuar, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Dragon fruit (Hylocereus polyrhizus) is a tropical fruit. Recently, it has gained interest from the public due to its potential beneficial effects on health. The acclimatization of micropropagated Hylocereus polyrhizus depends on the application of gibberellic acid (GA3 ) to increase plant growth. Eggshells are waste materials from industrial sectors, and they are composed of calcium source that is vital for the development of plant shoots and root. The objective of this research is to investigate the effect of different concentrations of GA3 and eggshell either added individually or in combination on the growth of shoot length and shoot diameter of H. polyrhizus. The result showed the shoot length of the H. polyrhizus increased by approximately 54.69%, from 0.64 ± 0.13 cm to 0.99 ± 0.26 cm, as the concentration of GA3 increased from 0 ppm to 10 ppm. Furthermore, this finding also reported that with eggshells, GA3 showed an adverse effect on the development of shoot diameter. The growth of shoot length and shoot diameter with the addition of eggshell was different, perhaps due to the gibberellic acid affecting the shoot length but not the shoot diameter. Generally, the growth of shoot length and shoot diameter with eggshells was higher in comparison with those without eggshells. With that, we can prove that eggshell is a good additive to promote the growth of H. polyrhizus.